Mental Health in Affectionate, Antagonistic, and Ambivalent Relationships During the COVID-19 Pandemic: A Latent Profile Analysis - Mehulić, Jasmina; Kamenov, Željka (Frontiers in Psychology, 2021)
The ongoing COVID-19 pandemic presents an acute stressor affecting mental health. In these stressful times, intimate relationship functioning could serve as a protective or risk factor to partners’ well-being. Adult Croatian citizens engaged in intimate relationships (N = 727) reported their relationship characteristics and assessed symptoms of depression, anxiety, and stress during the state lockdown in May 2020. Three relationship profiles based on variations in key relationship characteristics were identified using latent profile analysis. Profiles represented distinct relationship types described as affectionate, ambivalent, and antagonistic relationships. These relationship types differed in their levels of love, perception of partner’s humility and responsiveness as well as partner's behavior. Relationship type was associated with mental health symptoms during COVID-19 pandemic and state lockdown, such as depression, anxiety, and stress. Being in an affectionate relationship was associated with the lowest levels of depression, anxiety, and stress, and in an antagonistic relationship with the highest. Ambivalent relationships were characterized by moderate levels on all measured mental health indicators with no difference in anxiety compared to affectionate relationships. The results emphasized the link between relationship functioning and successful coping with mental health hazards such as the fear of disease or restrictive measures put in place to contain the COVID-19 pandemic.